Inmate Partner Violence Through Social Networks - Martinez-Lanz, Patricia; Cazares, Paulina Alanis; Kuri, Nathalie Aziz; Huerta, Michelle Duran; Araiza, Ana Leticia Perez; Valdez, Patricia Hernandez (European Scientific Journal, ESJ, 2016)
The purpose of this research was to analyze the relationship between dating violence and the social media. A sample of 400 university students from both private and public institutions of Mexico City was selected. From these sample, 46.6% were men and 52.4% women, with an age range of 16-29. Two scales were used to evaluate, the first one corresponds to violence in dating and the second scale to violence in dating through social media. Both instruments are Likert scale with response options ranging from strongly disagree to strongly agree. A pilot test was used to evaluate the usefulness of the instrument and its validness and reliability. Statistical analysis of Chronback alpha and factor analysis of the scales were used. In the reliability analysis appropriate values for both scales were obtained, which means that there was an appropriate relationship between the reagents with the scales proposed in general. To analyze the relationship between intimate partner violence and intimate partner violence on social media crosstabs were performed with analysis chi square, the results showed significant differences between dating violence and intimate partner violence on social media on significance levels. Thus, the relationship between intimate partner violence and intimate partner violence on social media showed that in a low (high) level of violence there is also a low (high) level of violence in social media likewise in a severe level of intimate partner violence the level of violence involving social media is also severe.